Islamic Wealth Planning through Saving and Investment Strategies for Productive and Retirement Life: Evidence from the Life-Cycle Financial Perspective - Zaskia Islamy (Institut Agama Islam Negeri Palopo, 2026)
Islamic wealth planning plays a crucial role in promoting long-term financial security for Muslim households during both productive and retirement stages. This study examines the integration of Islamic saving and Sharia-compliant investment strategies as a framework for achieving sustainable financial well-being across the life cycle. A qualitative library research approach was employed through a critical review of relevant literature, Islamic financial principles, and regulatory frameworks. The findings reveal that effective Islamic wealth planning depends more on financial discipline, clear financial goals, consistent saving behavior, and appropriate Sharia-compliant investment decisions than on income level alone. Guided by the principles of Maqāṣid al-Sharī‘ah, wealth is regarded as a trust (amanah) that should be managed ethically, productively, and sustainably. The integration of saving and investment enhances wealth accumulation, financial resilience, and retirement preparedness while supporting both economic and spiritual objectives. This study offers a conceptual framework that contributes to the advancement of Islamic wealth planning and sustainable financial decision-making. Keywords: Islamic financial planning, Islamic saving, investment of wealth, productive period, retirement period.